Effect of Malic Acid on Visceral Characteristics and Coliform Counts in Small Intestine in the Broiler and Layer Chickens - Moharrery, A.; Mahzonieh, M. (International Journal of Poultry Science, 2005)
Antimicrobial feed additives such as organic acids have made a tremendous contribution to the profitability in the intensive husbandry and providing people with healthy and nutritious poultry products. For examine of this effects of organic acids two experiments were conducted to determine the effects of the malic acid on chicken visceral characteristics and E. coli population in the small intestine. First study was performed with male egg type chickens (2 to 21 d of age) which received four levels of malic acid via drinking water. Malic acid was added to the water and offered to chicken freely from first to end of experiment with constant concentration in both experiments. The treatments were zero (as a control), 0.05, 0.10, and 0.15 percent of malic acid which dissolved in water and given to them in waterer pan. The chicks were slaughter on 21 days old and above parameters were measured on visceral organs. In second experiment broiler chicken (male and female from 1 to 56 d of age) was evaluated for same parameters on same treatments as a mentioned for the first experiment. No significant difference (P> 0.05) was observed between treatments for weight gain and liver percentage in both experiments. Difference between treatments in relation to gastrointestinal tract (GIT) percentage has been shown in Exp. 1 (p< 0.05). The results of these trials showed that malic acid have the potential for reduction of E. coli population in chicken intestine in both experiments.